3D Molecular Cytology of Hop (Humulus lupulus) Meiotic Chromosomes Reveals Non-disomic Pairing and Segregation, Aneuploidy, and Genomic Structural Variation - Easterling, Katherine A.; Pitra, Nicholi J.; Jones, Rachel J.; Lopes, Lauren G.; Aquino, Jenna R.; Zhang, Dong; Matthews, Paul D.; Bass, Hank W. (Frontiers in Plant Science, 2018)
Hop (Humulus lupulus L.) is an important crop worldwide, known as the main flavoring ingredient in beer. The diversifying brewing industry demands variation in flavors, superior process properties, and sustainable agronomics, which are the focus of advanced molecular breeding efforts in hops. Hop breeders have been limited in their ability to create strains with desirable traits, however, because of the unusual and unpredictable inheritance patterns and associated non-Mendelian genetic marker segregation. Cytogenetic analysis of meiotic chromosome behavior has also revealed conspicuous and prevalent occurrences of multiple, atypical, non-disomic chromosome complexes, including those involving autosomes in late prophase. To explore the significance and nature of this atypical chromosome behavior and its role in segregation distortion, we undertook 3D cytogenetic analysis of hop pollen mother cells stained with DAPI and FISH probes to track specific loci. We used telomere FISH to demonstrate that hop exhibits a normal telomere clustering bouquet. We also identified and characterized a new sub-terminal 180 bp tandem repeat family called HSR0, and showed that if found near the ends of chromosomes between HSR1 and the telomere. 5S rDNA FISH confirmed extensive departures from normal disomic signal composition and distribution. Anaphase chromosome bridges with interstitial telomere signals were also observed, suggestive of structural aberrations and non-disomic behavior. These findings implicate multiple phenomena, including aneuploidy, segmental aneuploidy, or chromosome rearrangements, as causal for known segregation distortion in hop.